D

#### [Algebra] Easiest way to solve this?

22 viewed last edited 4 years ago Hanna Owens
2
I have this formula 3x^(2) - 3 = 0 I know there are two answers for this, x = -1 and x = 1 I think I am missing some rule, or I am doing it wrong. What would be the most efficient or easiest way? I divided by 3 -> x^(2) -1 = 0 Then moved the 1 to the right, or +1 both sides -> x^(2) = 1 And then I took the square root on both sides so x = √1 Vivekanand Vellanki
0
Another way to solve is by factorising the equation. However, that also involves similar steps. Taking 3 as a common factor gives, 3(x^2 - 1)=0 Let \alpha and \beta be the roots of the equation x^2-1=0. Then, \alpha\beta=-1 and \alpha + \beta = 0 Giving \alpha = 1; and \beta = -1 Hence, the roots are x=\pm 1 Sangeetha Pulapaka
0
3 x{^2} - 3 = 0 can also be solved by using the addition propery of equality we add +3 to each side. 3 x{^2}- 3 + 3 = 0 + 3 which is 3x^{2}= 3 Now using the property of division or the division property of equality we divide each side by 3 \frac{3x^{2}}{3} =\frac{3}{3} we get x^{2} = 1 , x = +1 , -1